THE EFFECT OF PROCESS AND PRODUCT APPROACHES ON THE STUDENTS’ COMPETENCY IN WRITING DIFFERENT TYPES OF TEXTS - Ayu Wirawati, Ni Kadek; Tantra, Dewa Komang; Ratminingsih, Made (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
This study aims at finding the effect of process and product approaches to the eighth grade students of SMP Harapan 1 Denpasar on their  competency in writing different types of texts. This is an experimental study with post-test only comparison group design using 2 x 3 factorial design. The results of the study are: 1) there is a significant  difference of process and product approach on the students? writing competency, 2) there is a significant difference on the students? competency in writing narrative paragraph between process and product approach group, 3) there is a significant difference on the students? competency in writing recount paragraph between process and product approach group, 4) there is a significant difference on the students? competency in writing descriptive paragraph between   process and product approach group,5) there is an interaction between the writing approaches and types of texts. Keywords : Process Approach, Product Approach, Types of Texts and Writing Competency.